Thin film composite polyelectrolyte multilayer nanofiltration membrane fabricated using spin assisted layer by layer assembly: Application of solution diffusion film model - Alghamdi, Ahmad; Fadhillah, Farid (Communications in Science and Technology, 2020)
Thin Film Composite (TFC) Polyelectrolyte Multilayer (PEM) Nanofiltration (NF) membrane consisting of multilayer of Poly(diallyl dimethyl ammonium chloride) (PDAC) and Poly(sodium 4-styrenesulfonate) (PSS) deposited on polyethersulfone (PES) support was prepared using spin-assisted layer by layer assembly (SA-LbL). This work is an effort to discover new material having better characteristics and performance than commercial polyamide (PA) NF membrane. Two main operating conditions namely temperature and salt concentration were investigated and the effect of both on membrane performance was studied. Solution-diffusion Film Model (SDFM) membrane employing two fitting parameters i.e. membrane salt permeability (PS) and stagnant layer salt permeability PS(d), was used to explain membrane transport across the membrane. The result showed an good agreement between experimental and observed rejection rate suggests PEM membrane behaves similar to typical solution diffusion-type composite membrane and SDFM can be used to predict the membrane performance and behavior.